FOX NEWS SMEARS. - Warner, Melinda (AMASS, 2011)
The article discusses the fake stories of Fox News since 2004. It mentions the fake news stories about the manicure received by Senator John Kerry before a debate, the release of emails hacked from the Univesity of East Anglia on scientific data about global warming and news about sick people who could face death panels just to defeat the health care bill of Democrats. It also notes the rumors on a tragic Arizona wildfire and news about Chaz Bono that offended the transgender community.